SARS-CoV-2 Omicron variants: burden of disease, impact on vaccine effectiveness and need for variant-adapted vaccines - Pather, Shanti; Madhi, Shabir A.; Cowling, Benjamin J.; Moss, Paul; Kamil, Jeremy P.; Ciesek, Sandra; Muik, Alexander; Türeci, Özlem (Frontiers in Immunology, 2023)
The highly transmissible Omicron (B.1.1.529) variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first detected in late 2021. Initial Omicron waves were primarily made up of sub-lineages BA.1 and/or BA.2. BA.4 and BA.5 subsequently became dominant in mid-2022, and several descendants of these sub-lineages have since emerged. Omicron infections have generally caused less severe disease on average than those caused by earlier variants of concern in healthy adult populations, at least, in part, due to increased population immunity. Nevertheless, healthcare systems in many countries, particularly those with low population immunity, have been overwhelmed by unprecedented surges in disease prevalence during Omicron waves. Pediatric admissions were also higher during Omicron waves compared with waves of previous variants of concern. All Omicron sub-lineages exhibit partial escape from wild-type (Wuhan-Hu 1) spike-based vaccine-elicited neutralizing antibodies, with sub-lineages with more enhanced immuno-evasive properties emerging over time. Evaluating vaccine effectiveness (VE) against Omicron sub-lineages has become challenging against a complex background of varying vaccine coverage, vaccine platforms, prior infection rates, and hybrid immunity. Original messenger RNA (mRNA) vaccine booster doses substantially improved VE against BA.1 or BA.2 symptomatic disease. However, protection against symptomatic disease waned, with reductions detected from 2 months after booster administration. While original vaccine-elicited CD8+ and CD4+ T-cell responses cross-recognize Omicron sub-lineages, thereby retaining protection against severe outcomes, variant-adapted vaccines are required to expand the breadth of B-cell responses and improve durability of protection. Variant-adapted vaccines were rolled out in late 2022 to increase overall protection against symptomatic and severe infections caused by Omicron sub-lineages and antigenically aligned variants with enhanced immune escape mechanisms.